2022
DOI: 10.1002/nop2.1540
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis on the relationship between posttraumatic growth and resilience in people with breast cancer

Abstract: Aim To quantitatively synthesize the correlation between posttraumatic growth and resilience among breast cancer patients and explore the potential moderators affecting the relation. Design A meta‐analysis of cross‐sectional studies. Methods This meta‐analysis followed the Preferred Reporting Items for Systematic Review and Meta‐Analyses 2020 guidelines. This meta‐analysis was carried out by searching Chinese and English databases of China National Knowledge Infrastructure, WANFANG DATA, Chongqing VIP Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Additionally, as a secondary objective, we investigated potential moderators that may influence the strength of the association, including sample size, age, time since diagnosis, publication type, continent, FCR and PTG measurement tools, trauma roles, and gender. These factors were selected on the basis of previous studies, and the vast majority of them are thought to modulate the relationship between PTG or FCR and associates ( Marziliano et al, 2020 ; Ning et al, 2023 ; Wan et al, 2023 ). In addition to potentially helping to explain the inconsistency of the findings, these factors have the promise of providing a basis for the proper view of FCR to promote cancer-associated PTG in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, as a secondary objective, we investigated potential moderators that may influence the strength of the association, including sample size, age, time since diagnosis, publication type, continent, FCR and PTG measurement tools, trauma roles, and gender. These factors were selected on the basis of previous studies, and the vast majority of them are thought to modulate the relationship between PTG or FCR and associates ( Marziliano et al, 2020 ; Ning et al, 2023 ; Wan et al, 2023 ). In addition to potentially helping to explain the inconsistency of the findings, these factors have the promise of providing a basis for the proper view of FCR to promote cancer-associated PTG in the future.…”
Section: Introductionmentioning
confidence: 99%
“…In their meta-analysis, Wan et al (2022a) examined the relationship between PTG and resilience in breast cancer patients (17 studies, including 4,156 breast cancer patients) and found a high positive correlation between PTG and resilience, while Adamkovic et al (2022) examined the relationship between life satisfaction, PTG, ways of coping and resilience in cancer patients and found that increasing life satisfaction was strongly associated with resilience, moderately associated with ways of coping, and weakly associated with PTG. In a study conducted by Schmidt et al (2012) involving 54 cancer patients, it was discovered that having a secure attachment style was closely linked to positive reframing, active coping, and religion.…”
Section: Introductionmentioning
confidence: 99%